Beyond conventional MRI: diagnostic utility of diffusion and ADC mapping in seronegative spondyloartropathy - Lamiaa Arafat; Afaf Abd-Elkader Hassan; Samar H. Goma; Marwa Makboul; Shimaa Farghaly (Egyptian Journal of Radiology and Nuclear Medicine, 2026)
Abstract Background Seronegative spondyloarthropathies represent a broad spectrum of inflammatory disorders that affect articular and extra-articular structures. MRI is considered the gold standard for diagnosing sacroiliitis. Our study aims to evaluate the added advantages of DWI and ADC value over STIR in identifying acute sacroiliitis among seronegative spondyloarthropathy patients. Methods Seventy-five patients with clinically suspected acute seronegative spondyloarthropathy were included. Laboratory investigations, clinical evaluation, and disease activity scoring using the ASDAS and DAPSA systems were performed. MRI was done, then compared with clinical parameters. Results Bone marrow edema was the most frequent MRI finding among active group demonstrating high statistical significance (p < 0.001). Both DWI and ADC demonstrated greater ability to detect acute sacroiliitis with a p-value < 0.001 than STIR with a p-value=0.002. However, ADC had the highest specificity and accuracy by 100–89.4%, respectively, followed by DWI and STIR, according to the clinical scoring system. Also, ADC value demonstrates a strong positive correlation with a higher statistically significant differences compared to DAPSA scoring (r = 0.934, p < 0.001), followed by ASDAS-CRP scoring (r = 0.924, p < 0.001), then ESR_1st hr. (r = 0.713, p < 0.001), and CRP level (r = 0.684, p < 0.001). Conclusions Integrating DWI and ADC measurements into routine MRI protocols for sacroiliac joint assessment provides significant diagnostic benefits, as ADC can improve clinical management and confirm the acute inflammation especially when STIR is ambiguous or negative.